Optimization and Thermodynamic Studies of Lead (II) and Cadmium (II) Ions Removal from Water Using Musa acuminata Pseudo-Stem Biochar - Nimusiima, Daniel; Nalumansi, Irene; Mukasa, Paul; Byamugisha, Denis; Ntambi, Emmanuel (Green, 2023)
We recently found out that water from the Ugandan stretch of the Kagera transboundary river (East Africa) is contaminated with lead (Pb2+) and cadmium (Cd2+) ions at levels that are above permissible limits in drinking water. Because lignocellulosic biomass-based adsorbents have been explored for the remediation of metal ions from water, this study investigated the potential of Musa acuminata pseudo-stem (MAPS) biochar for the remediation of Pb2+ and Cd2+ ions from water. Batch adsorption experiments were performed to optimize the adsorption conditions while the isotherms were analyzed using Freundlich and Langmuir models. Results showed that the maximum adsorption capacity at equilibrium was 769.23 mg/g and 588.23 mg/g for Pb2+ and Cd2+ ions, respectively. Langmuir isotherm model provided the best fit for the data, and it was favorable since all r2 values (Cd2+ = 0.9726 and Pb2+ = 0.9592) were close to unity. Gibb’s free energy change was found to be negative for both metals, implying the feasibility of the adsorption process. Correspondingly, the enthalpy change was positive for both metal ions which revealed that the adsorption process was endothermic and it occurred randomly at the solid-liquid interface. These results suggested that biochar from MAPs could be utilized for the removal of Pb2+ and Cd2+ from polluted water in the Kagera transboundary river to make it suitable for domestic use. Further studies should consider chemical modification of the biochar as well as characterization to examine the chemical nature of the biochar.
Keywords: Adsorbent; Biochar; Lignocellulose; Heavy Metals; Water Treatment